A device to measure forces at the hands during the grab start - Cavanagh, P. R.; Palmgren, J. V.; Kerr, B. A. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
It was the purpose of this study to design, construct, and make a preliminary evaluation of a device to measure the forces exerted by the hands during the performance of the grab start in competitive swimming.